A Study of a Certain Family of Multivalent Functions Associated with Subordination - Rasheed, Reem O.; Jassim, Kassim A. (Iraqi Journal of Science, 2021)
The aim of this paper is to introduce a certain family of new classes of multivalent functions associated with subordination. The various results obtained here for each of these classes include coefficient estimates radius of convexity, distortion and growth theorem.